Technical Review of Fin Addition Analysis of Air Intake Valve on Gas-Oil Fuel Engine - Semin Semin; Linggar Palang Aras RFC; Beny Cahyono; Nilam Sari Octaviani (Institut Teknologi Sepuluh Nopember, 2018)
Modification of single-fuel diesel engine into dual-fuel diesel engine has been done by researchers to solve the problem of depletion petroleum reserves. Even the problem petroleum reserves are projected to be exhausted in the next 50 years. Gas-Oil fuel engine focus on solar-CNG as a fuel. Explanation of the difference in the fuel ratio of diesel engines with Gas-Oil fuel diesel engines has considerable differences. The factors that are discussed here are the factors of mixing air and fuel. The amount of fuel in the Gas-Oil fuel diesel engine causes an increase in the gas fuel mass flow rate (CNG), although with the addition of fuel gas, the mass flow rate of diesel oil is reduced. In this paper, the Gas-Oil fuel engines research and development fueled using solar-CNG are highlighted to keep the performance of the engine. Modification focused on air intake valve to give maximum turbulent flow ratio and effect on increasing Gas-Oil fuel engine performance. The high activities for future Gas-Oil fuel engines research and development to meet future Gas-Oil fuel engine solar-CNG is recorded in the paper.